GRAPHIC ILLUSTRATIONS OF CHINESE AND UKRAINIAN CHILDREN'S BOOK EDITIONS OF THE LATE 20TH CENTURY: INSPIRATIONS AND ARTISTIC FEATURES - Ван , Ханьпін (Art and Design, 2024)
Purpose: scientific coverage of the artistic features of Chinese and Ukrainian illustrations in children's books editions of the late 20th century with a comparative analysis of the author's approaches regarding formal-figurative, compositional, stylistic, coloristic and other principles, which the authors of both countries operate in the corresponding creative field of art. Methodology. To solve the set goal, the scientific research has used general scientific methods: cultural-historical, structural-typological, scientific-interpretive, formal-descriptive, the method of comparative analysis of author's concepts of creativity. When directly examining samples of book illustrations, the work uses the method of art analysis, which includes consideration of structural elements of compositions, stylistics, color solutions, etc. The results. The topic of illustrated children's publications attracts the attention of many researchers both in China and in Ukraine, but there are no publications that systematize the creative approaches of artists of both countries of the respective direction in a comparative aspect. To implement this task, literary sources outlining the historical development of the genre of children's books illustration in China and Ukraine at the end of the 20th century have been analyzed. Thanks to this, the conceptual similarity or uniqueness of the author's approaches of illustrators of children's books in the two countries is revealed. Accordingly, the methods of graphic solution of illustrative cycles have been analyzed and their artistic characteristics are summarized. Scientific novelty. For the first time in the art history of China and Ukraine, an attempt will be made to compare the approaches of the artists of both countries to the artistic solution of illustrations of children's books editions of the end of the 20th century, as well as a scientific qualification of a number of monuments of graphic art of the corresponding type of printed products. Practical significance. The enrichment of the figurative language of the illustration of children's books by Chinese and Ukrainian artists has been taking place due to the deepening of the conceptual connection of formal expressive means with the corresponding national cultural traditions. This confirms the expediency of continuing systematic studies of this art history issue based on the work of modern illustrators of China and Ukraine.